Seasonal incidence of fruit borer, Helicoverpa armigera (Hub.) in tomato in relation to weather parameters - Singh, Narendra; Dotasara, S. K.; Jat, Sanwar Mal; Naqvi, A. R. (Annals of Agricultural Research, 2018)
A field experiment was conducted at farm of Agricultural Research station, Swami Keshwan andRajasthan Agricultural University, Bikaner, during the 2013-14, rabi season, to study seasonalincidence of tomato fruit borer, Helicoverpa armigera. Tomato fruit borer, H. armigera is a well knownpolyphagous insect. The larvae feed on the leaves and bore into fruits, thereby causing severe damageto the crop and significant losses in yield. Besides tomato, it is a regular pest of chickpea and cotton.The incidence of fruit borer started in the last week of December on tomato. The population lowereddown upto 3rd SMW (Standard Meteorological Week) and thereafter, population increased butfluctuating trend was recorded upto 9th SMW. The larval population increased and reached to peakin 12th SMW. Thereafter, it's population decreased gradually and negligible population was recordedupto second week of April. A significant positive correlation was observed between pest populationand maximum and minimum temperature, whereas, it was non-significant positive with averagerelative humidity. A non-significant negative correlation was computed between pest populationand total rainfall.